The effect of project-based training on recycling awareness level - Cebi, Hicret; Arslan, Mustafa (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
In this study, the effect of project-based learning (PBL) on the recycling awareness levels of middle school students was investigated. The study was conducted with two groups of seventh-grade students with similar academic achievement levels. A quasi-experimental design was used, where the experimental group received project-based recycling education, while the control group was taught using traditional methods from the 2018 Ministry of National Education (MoNE) curriculum. Before and after the 'Household Waste and Recycling' topic was covered, the 'Recycling Awareness Scale' was applied to both groups. The results showed no significant difference in recycling awareness levels between the groups before the training. However, after the training, the experimental group demonstrated a statistically significant increase in recycling awareness compared to the control group. The findings suggest that project-based learning is an effective method for enhancing recycling awareness among middle school students. It is recommended that future studies explore the use of PBL in different subjects and grade levels to further validate its effectiveness.
Keywords: Project-based learning; recycling; awareness; middle school students; Environmental Education; Education & Educational Research